2019
DOI: 10.3390/cells8010065
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Insults and Mitochondrial DNA Mutation Promote Enhanced Autophagy and Mitophagy Compromising Cell Viability in Pluripotent Cell Model of Mitochondrial Disease

Abstract: Dysfunction of mitochondria causes defects in oxidative phosphorylation system (OXPHOS) and increased production of reactive oxygen species (ROS) triggering the activation of the cell death pathway that underlies the pathogenesis of aging and various diseases. The process of autophagy to degrade damaged cytoplasmic components as well as dysfunctional mitochondria is essential for ensuring cell survival. We analyzed the role of autophagy inpatient-specific induced pluripotent stem (iPS) cells generated from fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 61 publications
2
39
0
Order By: Relevance
“…The interactions and relationships among autophagy, pyroptosis and ERS-mediated apoptosis have been widely studied, as Li et al have reported that autophagy protected HUVECs against ER stress-mediated apoptosis (Li et al, 2019). Increasing evidence demonstrates that hypoxic/ ischemic conditions lead to mitochondrial injury (Zuo et al, 2014) and that damaged mitochondria lead to a massive accumulation of ROS (Lin et al, 2019a). Studies have clarified that the massive accumulation of ROS can induce the NLRP3 inflammasome and subsequently trigger caspase-1-dependent pyroptosis (Qiu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The interactions and relationships among autophagy, pyroptosis and ERS-mediated apoptosis have been widely studied, as Li et al have reported that autophagy protected HUVECs against ER stress-mediated apoptosis (Li et al, 2019). Increasing evidence demonstrates that hypoxic/ ischemic conditions lead to mitochondrial injury (Zuo et al, 2014) and that damaged mitochondria lead to a massive accumulation of ROS (Lin et al, 2019a). Studies have clarified that the massive accumulation of ROS can induce the NLRP3 inflammasome and subsequently trigger caspase-1-dependent pyroptosis (Qiu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence demonstrates that the secondary injury stage after SCI is closely related to mitochondrial injury and excessive ROS generation [54]. Damaged mitochondria leads to a massive accumulation of ROS, which can induce NLRP3 in ammasome activation and subsequently trigger caspase-1-dependent pyroptosis [55,56]. Mitophagy, a selective autophagic degradation of damaged mitochondria [57], can reduce ROS accumulation [58,59], and may play a central role in curtailing pyroptosis following SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic neurons are more susceptible to mPTP activation than other cells because they are particularly common in aging, causing the overactivation of mPTP, thereby leading to cell death [ 237 ]. The overactivation of autophagy/mitophagy is a major factor in a variety of other neurodegenerative diseases [ 238 ].…”
Section: Mitophagy Aging Mptp and Parkinson’s Diseasementioning
confidence: 99%